Adaptive Immunity Regulation and Cerebral Ischemia - Qin, Xingping; Akter, Farhana; Qin, Lingxia; Cheng, Jing; Guo, Mei; Yao, Shun; Jian, Zhihong; Liu, Renzhong; Wu, Songlin (Frontiers in Immunology, 2020)
Stroke is a disease that occurs due to a sudden interruption of the blood supply to the brain. It is a leading cause of death and disability worldwide. It is well-known that the immune system drives brain injury following an episode of ischemic stroke. The innate system and the adaptive system play distinct but synergistic roles following ischemia. The innate system can be activated by damage-associated molecular patterns (DAMPs), which are released from cells in the ischemic region. Damaged cells also release various other mediators that serve to increase inflammation and compromise the integrity of the blood–brain barrier (BBB). Within 24 h of an ischemic insult, the adaptive immune system is activated. This involves T cell and B cell-mediated inflammatory and humoral effects. These cells also stimulate the release of various interleukins and cytokines, which can modulate the inflammatory response. The adaptive immune system has been shown to contribute to a state of immunodepression following an ischemic episode, and this can increase the risk of infections. However, this phenomenon is equally important in preventing autoimmunity of the body to brain antigens that are released into the peripheral system as a result of BBB compromise. In this review, we highlight the key components of the adaptive immune system that are activated following cerebral ischemia.